Phase I trial of HuMax-IL8 (BMS-986253), an anti-IL-8 monoclonal antibody, in patients with metastatic or unresectable solid tumors. Issue 1 (5th September 2019) - Bilusic, Marijo; Heery, Christopher R.; Collins, Julie M.; Donahue, Renee N.; Palena, Claudia; Madan, Ravi A.; Karzai, Fatima; Marté, Jennifer L.; Strauss, Julius; Gatti-Mays, Margaret E.; Schlom, Jeffrey; Gulley, James L.
Abstract : Background: HuMax-IL8 (now known as BMS-986253) is a novel, fully human monoclonal antibody that inhibits interleukin-8 (IL-8), a chemokine that promotes tumor progression, immune escape, epithelial-mesenchymal transition, and recruitment of myeloid-derived suppressor cells. Studies have demonstrated that high serum IL-8 levels correlate with poor prognosis in many malignant tumors. Preclinical studies have shown that IL-8 blockade may reduce mesenchymal features in tumor cells, making them less resistant to treatment. Methods: Fifteen patients with metastatic or unresectable locally advanced solid tumors were enrolled in this 3 + 3 dose-escalation trial at four dose levels (4, 8, 16, or 32 mg/kg). HuMax-IL8 was given IV every 2 weeks, and patients were followed for safety and immune monitoring at defined intervals up to 52 weeks. Results: All enrolled patients (five chordoma, four colorectal, two prostate, and one each of ovarian, papillary thyroid, chondrosarcoma, and esophageal) received at least one dose of HuMax-IL8. Eight patients had received three or more prior lines of therapy and five patients had received prior immunotherapy. Treatment-related adverse events occurred in five patients (33%), mostly grade 1. Two patients receiving the 32 mg/kg dose had grade 2 fatigue, hypophosphatemia, and hypersomnia. No dose-limiting toxicities were observed, and maximum tolerated dose was not reached. Although no objective tumor responses were observed, 11 patients (73%) had stable disease with median treatment duration of 24 weeks (range, 4–54 weeks). Serum IL-8 was significantly reduced on day 3 of HuMax-IL8 treatment compared to baseline ( p  = 0.0004), with reductions in IL-8 seen at all dose levels. Conclusions: HuMax-IL8 is safe and well-tolerated. Ongoing studies are evaluating the combination of IL-8 blockade and other immunotherapies. Trial registration: NCTN, NCT02536469 . Registered 23 August 2015, https://clinicaltrials.gov/ct2/show/NCT02536469?term=NCT02536469&rank=1 .